Sindrom Fahr: Kalsifikasi Intraserebral Patologis - Dewa Gede Putra Angga Pradnyana; Sarita Sharchis (Cermin Dunia Kedokteran, 2024)
Fahr’s syndrome is a collection of symptoms accompanied by symmetrical and bilateral abnormal calcification in the basal ganglia, thalamus, dentate nucleus, cerebral cortex, cerebellum, and hippocampus. Fahr syndrome can occur in young to middle-aged adults. Some of the most important etiologies are endocrine disorders, infections, and autoimmune diseases. The clinical symptoms are very diverse. Diagnostic criteria are established. One of the routine imaging examinations is a head CT scan. There is no specific therapy for Fahr syndrome, the treatment focuses on the symptoms and the underlying disease.